Implementasi metode sugestopedia untuk meningkatkan keterampilan menulis teks eksposisi - Niswatun Ngafifah; Siti Wahyuningsih; Riyadi Riyadi (Didaktika Dwija Indria, 2019)
Abstract. The purpose of research is to improve the exposition text writting skills used suggestopedia method. This research is Classroom Action Research with two cycles. The subjects of this research is the students of Setono primary education number 95 in the 2018/2019 academic years with 34 students. The techniques accumulation of data are observation, interview, document analyzing, and test. The analyze of data using triangulation technique, triangulation sources, and content validation. This research used an interactive analyze of miles-Huberman data analysis.  The result of the exposition text writing skills of students on cycle one the clasiccal results are 55,88% in the aspect of diction, 26,47% in the aspect of spelling and writting, 79,41% in the aspect of compability between  content and theme, 47,06% in the aspect of text structure, and 91,18% in the aspect of function text. While on the cycle two the classical results are 85,29% in the aspect of diction, 85,29% in the aspect of spelling and writting, 100% in the aspect of compability between  contents and theme, 85,29% in the aspect of text structure, 100% in the aspect of function text. It showed that the implementation of suggestopedia method can improve the exposition text writting skills.